Mesalamine-induced eosinophilic pleural effusion. Issue 4 (16th April 2020) - Al-abcha, Abdullah; Raziq, Fazal; Kherallah, Shouq; Alratroot, Ahmad
Abstract : A 45-year-old woman with a medical history of ulcerative colitis (UC) presented with difficulty in breathing. The patient was diagnosed with UC a month prior to presentation and was started on mesalamine suppository. Chest x-ray (CXR) on presentation showed bilateral pleural effusion, which was confirmed on CT angiogram of the chest. Diagnostic and therapeutic thoracentesis was performed and 0.7 L of pleural fluid was removed from the left side. The pleural fluid analysis was consistent with exudative pleural effusion with eosinophilia. Symptomatic improvement was noted after thoracentesis. Mesalamine was stopped and repeat CXR was obtained on the follow-up visit, which showed no pleural effusion. The Naranjo score was calculated to be 7, indicating that the eosinophilic pleural effusion was most probably secondary to adverse reaction from mesalamine.